Asymmetric Information in New Investment: Evidence in Indonesia - Yulianto Arief; Widiyanto Widiyanto; Witiastuti Rini (Foundations of Management, 2023)
Intra-industry sectors are producers of asymmetric information, which in turn has an impact on capital structure decisions. The purpose of this study was to determine (1) differences in debt-equity ratio, growth opportunities, firm age, and firm size as firm characteristics and (2) differences in the effect of growth opportunities, firm age, and firm size on the debt-equity ratio between manufacturing and nonmanufacturing firms. We collected 3,063 observation units consisting of 2,628 manufacturing sectors and 435 non-manufacturing sectors in the Indonesia Stock Exchange (IDX) and trimmed the data to eliminate the top and bottom 20%. Manufacturing firms are older and more stable, using their profitability to increase information disclosure. Although they produce lower asymmetric information, they do not prefer external financing as an effort to reduce intervention. In contrast, non-manufacturing firms have less tangible assets as a proportion of their total assets than manufacturing firms and therefore produce less asymmetric information of intrinsic value (tangible assets). As a result, manufacturing firms prefer debt issues over equity issues when financing new investments.